Micrurus Nigrocinctus (Central America Coralsnake) Predation - Muñoz, Manolo (2019)
Coral snakes and their mimics are rarely preyed upon by birds. Turquoise-browed Motmots and Great KisKadees, wich feed on snakes and other reptiles, avoid models with the patterns of coral snakes or their mimics. Howerver, predation on coral snakes by birds has been reported several times, especially Laughing Falcons, which may be the main avian predators of these snakes.